God and Spiritual Beings in the Cirebon- Javanese Belief System: A Reluctant Contribution against the Syncretic Argument - Muhaimin AG. (Studia Islamika, 1996)
The study of Javanese Islam has given rise to a controversy between those who deny the strong influence of Islam on the local culture, and they are looking the other way. The first group of many arguments based on deterministic mindset historical-psychological situation of the engineering community as well as Java. This mindset has weakened in line with studies done on Javanese Islam more deeply and critically by both groups. The findings showed that both groups of Islamic turns out to have a strong influence in the cultural roots of the local community.System-Cirebon Javanese belief, for example, no indication of syncretism. They do not have a concept of God that is different from Islam. The terms are not derived from the traditions of Islam, such as prayer or prince, it can be found; but is not a key element in building their confidence. Instead, the entire contents of the trust and the local community has its roots in line with Islamic tradition orthopraxy. Almost everything has a grounding and validation that comes from the grip of Islam: the Qur'an, the Hadith and the interpretations of scholars.DOI: 10.15408/sdi.v3i2.806